FORTIFICATION OF MORINGA OLEIFERA FLOUR ON QUALITY OF WET NOODLE - Prayitno, Sutrisno Adi; Galih Patria, Domas; Mardiana, Nur Agustin; Utami, Dwi Retnaningtyas; Kusumawati, Rinda; Rochma, Nurtalitha Alifia; Niam, Muhammad Khoirun (Food Science and Technology Journal (Foodscitech), 2022)
Noodles are foods that are often consumed by the public and contain a lot of carbohydrate compounds. Human needs are not only for carbohydrates but also for protein, fat, or mineral compounds. The need for macronutrients or minerals is not only found in flour sources, but can be obtained from natural sources such as Moringa oleifera leaves. It is known that Moringa oleifera leaves have nutritional, mineral or antioxidant potential and other bioactive. The purpose of this study was to determine the levels of macronutrients, crude fiber, and minerals (Ca and Fe) contained in wet noodles added (fortified) with Moringa oleifera leaves flour. In this study, the experimental design used a completely randomized design (CRD). The treatment carried out in the study was using 100% wheat flour as a control, 5% Moringa oleifera leaves flour, and 95% wheat flour, 10% Moringa oleifera leaves flour and 90% wheat flour, 15% Moringa leaves flour, and 85% wheat flour. The results showed that the addition of higher concentrations of Moringa oleifera flour resulted in differences in crude fiber, macronutrients and minerals in wet noodle products. Increasing the concentration of Moringa oleifera flour used also has a different effect on the sensory parameter of noodles. It is recommended that the use of Moringa oleifera flour does not exceed 5% because it is greatly affects the organoleptic of the product. Concentrations of 5%, 10%, and 15% have potential to increase macronutrients and minerals in noodle products. So it can be confirmed that Moringa oleifera leaves have the potential as a source of functional food. Key words: Noodles, Moringa oleifera, macro nutrition, minerals